Consumer Protection in Cash-Based Motor Vehicle Transactions: An Empirical Socio-Legal Study in Lhokseumawe, Indonesia - Zulkifli Zulkifli; Arief Rahman (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
This study examines the effectiveness of consumer protection law enforcement in cash-based motor vehicle transactions in Lhokseumawe, Indonesia. Despite the normative guarantees provided by Law No. 8 of 1999, cash consumers continue to face structural and behavioral barriers in practice. Using an empirical socio-legal approach with a mixed-methods design, this research draws on survey data from 100 consumers and in-depth interviews with key stakeholders, including dealers and regulatory authorities. The findings reveal a significant implementation gap, where legal enforcement remains largely symbolic. A “credit-centric bias” among dealers systematically disadvantages cash buyers through limited unit availability, slower administrative processes, and restricted access to information. Additionally, weak institutional oversight and the absence of active consumer advocacy organizations contribute to a regulatory vacuum that allows such practices to persist. Low levels of consumer legal literacy further exacerbate the problem, leading to a condition of “false rights fulfillment,” where consumers perceive their rights as satisfied despite experiencing procedural discrimination. This study concludes that improving consumer protection requires a shift from passive to proactive regulatory enforcement, supported by stronger institutional supervision and the development of local advocacy mechanisms. The findings contribute to a deeper understanding of how economic incentives can undermine the practical effectiveness of consumer protection law in emerging markets.